Corporate Accountability In Crime of Licensing By Law Number 10 of 1998 On Banking - Bastianto Nugroho (Faculty of Law, Merdeka University Surabaya, 2017)
Corporate development as development actors increasingly play an important role in people's lives. Therefore doubts in the past to place the corporation as a subject of criminal law to commit criminal acts and accountable in criminal law, has now shifted. The doctrine of non potest delinquere university (the corporation may commit a criminal offense) began to be abandoned by accepting corporate responsibility as a maker of criminal offenses in addition to the natural man. Determination of corporate responsibility as a maker of criminal offenses in the criminal law seems to have become demands of the times who could not be ignored to improve the state's responsibility to manage our increasingly complex society, as it appears in the manuscript draft Penal Code which have reached the stage of receiving and formulating the corporation as subject follow criminal and criminally responsible. Polemics appear along espoused corporate responsibility in criminal law. For that planning must include planning and enforcement aimed at providing legal protection for people against lawlessness and crime. Also keep in mind that the development of society and modernization brings great influence in the makeup of the community was included in the law. This research use method approach of law (statute approach) and the conceptual approach (conceptual approach).Approach legislation (statute approach) that solve the solution of the question by relying on the provisions of the legislation and regulations relevant conceptual approach (conceptual approach) that solves the answers to the formulation of the problem posed by referring to the concept of legal principles relevant.